THE PROBLEM OF CULTURAL EQUIVALENCE IN TRANSLATION - Mukhlisa Abdurazokova Abdurakhmon Qizi; PhD, Associate Professor Sitora Turaboyeva Zokir Qizi (Western European Studies, 2025)
The article explores the problem of cultural equivalence in translation, focusing on the comparative analysis of English and Uzbek languages. It examines the theoretical foundations of translation and highlights how cultural and linguistic differences influence the process of conveying meaning across languages. The study emphasizes that translation is not only a linguistic act but also a cultural negotiation, requiring the translator to act as a mediator between two distinct worldviews. The paper discusses the main challenges in achieving cultural equivalence and reviews strategies such as adaptation, explication, and cultural mediation.
Keywords: translation; cultural equivalence; untranslatability; intercultural communication